A utilização do Chat GPT e o processo de alfabetização científica e tecnológica no mundo contemporâneo - Carvalho, Gabriel Cardoso (Universidade Federal de São Carlos, 2023)
Currently, it is often observed that artificial intelligence is one of the most discussed subjects around the world. The new technologies are presented in a very abrupt way to society, and often this presents itself as a problem to be fought, considering that lately there is a lot of trust in the information present online, which is a problem, because the search for complete information and veracity of information is increasingly scarce. The ChatGPT tool shows itself as a positive and useful tool in a lot of aspects, but it also presents itself as a negative tool, considering the possibility of false information. It is not really discussed the right use of this kind of tool, which is being considered a possible problem for the professionals in education who are having problems with their students, considering that most of the answers are copied from the ChatGPT. Nevertheless, the great problem observed is the lack of critical sense and the right instruction to use this tool, because the answers are wrong most of the time, which is a problem for the formation of the student. Knowing about this problem, it is necessary to observe and qualify the usage of this kind of tool and then observe how the scientific and technological literacy is presented in the formation of the users. For that, a formulary was distributed to observe how people asked the questions to the tool, and then analyzes, based on scientific and technological literacy, which fundamentals are presented when people use this kind of tool. 35 answers were obtained, and the analysis of the answers was based on a categorization method. In the answers obtained from the formulary, it was possible to observe important aspects of the scientific and technological literacy defended by Fourez, such as the good use of specialists, the opening of black boxes, the use of simple models, the good use of translations, the use of interdisciplinary knowledge, and the good articulation between knowings.
The use of Chat GPT and the process of scientific and technological literacy in the contemporary world
Keywords: Inteligência artificial; Chat GPT; Alfabetização científica e tecnológica; Artificial inteligence; Scientific and technological literacy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO